Changes in Serum Fatty Acid Composition and Metabolome-Microbiome Responses of Heigai Pigs Induced by Dietary N-6/n-3 Polyunsaturated Fatty Acid Ratio - Wang, Liyi; Nong, Qiuyun; Zhou, Yanbing; Sun, Ye; Chen, Wentao; Xie, Jintang; Zhu, Xiaodong; Shan, Tizhong (Frontiers in Microbiology, 2022)
Changing n-6/n-3 polyunsaturated fatty acids (PUFAs) ratio is a potential nutritional strategy to improve pork quality. However, the effect of different n-6/n-3 PUFA ratios on serum fatty acid composition, microbiota and their metabolites in intestine of pigs remains unclear. Our study investigated the changes on serum fatty acid composition and metabolome-microbiome responses induced by dietary n-6/n-3 PUFA ratio based on a Heigai-pig model. A total of 54 Heigai finishing pigs (body weight: 71.59  2.16 kg) fed with 3 types of diets (n-6/n-3 PUFA ratios are 8:1, 5:1, and 3:1) were randomly divided into 3 treatments with 6 replications (3 pigs per replication). Results showed that dietary n-6/n-3 PUFA ratio significantly affected biochemical immune indexes including glucose (Glu), triglyceride (TG), total cholesterol (TChol), non-esterified fatty acid (NEFA), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and total thyroxine (TT4) and medium- and long-chain fatty acid composition especially n-3 PUFA and n-6/n-3 PUFA ratio in serum. However, no significant effects were found in the SCFAs composition and overall composition of gut microbiota community. In low dietary n-6/n-3 PUFA ratio group, the relative abundance of Cellulosilyticum, Bacteroides and Alloprevotella decreased, Slackia and Sporobacter increased. Based on metabolomic analysis, dietary n-6/n-3 PUFA ratio altered the metabolome profiles in the colon. Moreover, Pearson’s correlation analysis indicated that differential microbial genera and metabolites induced by different n-6/n-3 PUFA ratio had tightly correlations and were correlated with the n-6 PUFA and n-3 PUFA content in longissimus dorsi muscle (LDM) and subcutaneous adipose tissue (SAT). Taken together, these results showed that lower dietary n-6/n-3 PUFA ratio improved serum fatty acid composition and metabolome-microbiome responses of Heigai pigs and may provide a new insight in regulating metabolism of pigs and further better understanding the crosstalk with host and microbes in pigs.